Aplicação de um modelo cinemático tridimensional para predição de volume corrente em recém-nascidos: um estudo piloto - Araújo, Ana Gabriela de Figueiredo (2019)
Background: Chest movement quantification and noninvasive monitoring have been useful in evaluation of newborn (NB) lung function. Different methods have already been tested, however, there is little progress regarding the agreement of these new tools in neonatal practice. Aim: To evaluate the agreement between the tidal volume (TV) estimated by the three-dimensional analysis of the thoracoabdominal movement in the Matlab® software and the TV predicted by the body weight of term newborns (NBs). Methods: This is a pilot methodological study with NBs filmed for two minutes in a dorsal position and maximal exposure of the thoracoabdominal region. TV (in ml) was estimated from the threedimensional analysis of thoracoabdominal movement in the Matlab® and compared to the predicted TV per kilogram of weight for each NB (5 ml/kg), on a Bland-Altman plot. Results: Thirteen NBs (gestational age: 39.1±0.8 weeks), with a mean weight and length of 3175.4±493.8g and 49±2.8cm, respectively, were included in the study. TV estimated by the kinematic analysis was 16.3±4.2 ml or 5.1 ml/kg and 15.9±2.5 ml or 5 ml/kg according to the calculation for the predicted value for weight. The difference between the means of the studied values was 0.4 ml (bias), with p=0.624 and confidence interval of -5.2 to 6.0 ml. Conclusions: The methods for TV measuring are interchangeable in this sample of NBs, suggesting that the threedimensional analysis of thoracoabdominal motion in Matlab® software can estimate the TV of terms NBs, in a simple, fast and noninvasive way. Thus, the evaluation by Matlab® is promising and should be tested with methods that are gold standard for TV evaluation.